Family and mental health - Arévalo, Victoria (2001)
The family is the group in which individuals develop different links among them the affective one. Several cultural and valuable aspects are transmitted and protected among them. The conductual cognitive familiar therapy is focused on the adolescent and the therapeutic intervention